Employment Incentives: Issues and Solutions - Yoonsoo Park (Korea Development Institute (KDI), 2016)
As of 2016, 20 employment incentives are in operation in Korea under four ministries with a budget of 2.8 trillion won. However, instead of creating new jobs, these projects mainly aim to maintain and improve existing jobs, unlike most OECD countries. Moreover, the scope of target groups is too broad and conflicts with the core principle of providing selective support to vulnerable job seekers. Therefore, efforts must be made to enhance policy efficiency by placing stronger emphasis on new job creation and support for the vulnerable. - As of 2016, 20 employment incentives are currently in operation under four ministries with a budget of 2.8 trillion won. - This paper discusses the effects and limitations of Korea's employment incentives and intends to suggest a direction for improvement. - Employment incentives are government- subsidized budgetary projects that aim to increase employment throughout the economy. - According to the OECD, employment incentives are classified into three types: recruitment incentives, employment maintenance incentives and job rotation and sharing. - Under normal conditions, recruitment incentives are effective, but at a time of crisis, maintenance incentives and job rotation and sharing projects could serve as effective policy measures. - The abuse of employment incentives would lead to several side effects, and thus should be used selectively for the vulnerable who are in desperate need of government support. - Korea's budget for employment incentives relative to GDP is lower than the OECD average but higher than advanced economies in the West, such as the US, the UK, Germany and France. - OECD countries have operate employment incentives to complement new hiring, whereas Korea focuses on maintaining and improving existing jobs. - According to a multiple choice survey conducted on operators of employment incentives regarding the main beneficiaries, 'no particular target' was the most common answer. - Analysing the target selection process used in major employment incentives reveals a lack of selective support for the vulnerable. - The final goal of employment incentives, must be clarified further, and more support should be given to new jobs. - One suggestion for selective support is to grant a subsidy to only for those who have engaged in job seeking activities via employment support programs for a certain period of time but have failed to find employment.
Keywords: 330